Parenting and child adjustment: a comparison of Turkish and English families. Issue 3 (3rd July 2019) - Aytac, Berna; Pike, Alison; Bond, Rod
ABSTRACT: The links between parenting and child behaviour in cultural context have received increasing research attention. We investigated the effect of parenting on child adjustment using a multi-method design, comparing English and Turkish families. The socioeconomically diverse samples included 118 English and 100 Turkish families, each with two children aged 4–8 years. Mothers completed questionnaires as well as parent–child interaction being assessed using a structured Etch-a-Sketch task with each child separately. Children were interviewed about their relationships with their mothers using the Berkeley Puppet Interview. Multiple-group Confirmatory Analysis was used to test Measurement Invariance across groups, and a multi-informant approach was used to assess parenting. We found partial cross-cultural measurement invariance for parenting and child adjustment. Strikingly, the association between parenting and child adjustment was stronger among English families than Turkish families. Culturally distinct meanings of both parenting and child behaviour must be considered when interpreting their association.